Key factors associated with quality of postnatal care: a pooled analysis of 23 countriesResearch in context - Shuangyu Zhao; Yixuan Zhang; Angela Y. Xiao; Qiwei He; Kun Tang (EClinicalMedicine, 2023)
Summary: Background: Progress in reducing maternal and neonatal mortality, particularly in low-income and middle-income countries (LMICs) and regions, is insufficient to achieve the Sustainable Developmental Goals by 2030. High-quality postnatal care (PNC) for mothers and neonates is crucial for mothers and babies, yet it remains the most neglected intervention on the continuum of maternal and child care. We aimed to estimate the associations between observable factors and high-quality maternal and neonatal PNC in pooled and country-specific analyses. Methods: In this cross-sectional study, we used the most recent (2015–2022) Demographic and Health Surveys from 23 countries across Africa (n = 14), Southeast Asia (n = 3), Eastern Mediterranean (n = 2), Europe (n = 2), Americas (n = 1), and Western Pacific (n = 1). Women who, within the last 5 years, were aged 15–49 years at their last live birth that had delivered a singleton child were included. We identified eleven PNC behaviours recommended by the World Health Organization (WHO) to measure PNC quality, and applied thresholds to create binary outcomes for quality maternal and neonatal PNC. 15 factors were included in our analysis to assess their association with high-quality PNC for mothers and neonates in a series of single-adjusted and mutually adjusted logistic regression models, both in pooled and country-specific analysis. We also conducted two sets of subgroup analyses for place of residence and maternal age at last birth, and two sets of supplementary analyses to test the robustness of the results. Findings: Among 172,526 women and their most recent child, 41.42% (40.93–41.91) received quality maternal PNC while 42.34% (41.86–42.83) received quality neonatal PNC. In the pooled analysis, we found that the factors showing the strongest associations with quality maternal PNC were delivery by skilled birth attendants (SBAs) (OR: 4.92; 95% CI: 4.32–5.59), four or more antenatal care (ANC) visits (OR: 1.69, 1.58–1.81), and institutional delivery (OR: 1.61; 1.46–1.78). Consistent results were found for all factors of quality newborn care (e.g., delivery by SBA: OR, 4.25; 3.75–4.81; four or more ANC visits: OR, 1.83; 1.70–1.96) except institutional delivery. The association between these leading factors and PNC quality were broadly consistent across countries. Subgroup analyses and sensitivity analyses showed generally consistent results. Interpretation: Our study demonstrated that institutional delivery and frequent ANC visits had the strongest positive associations with quality PNC for both mothers and neonates. Our findings highlight that improvements to the quality of maternal and neonatal PNC in the LMICs we assessed are urgently needed to achieve ambitious maternal, newborn, and child health goals. Funding: China National Natural Science Foundation.